Bovine Hypodermatosis: Diagnosis, Treatment and Prevention (review) - A. A. Glazunova; O. V. Kustikova; D. A. Lunina; P. V. Ilyasov (Российский паразитологический журнал, 2019)
The purpose of the research is to analyze the literature in the Hypodermа bovis morphology and biology, as well as clinical features and advanced techniques for diagnostics, prevention and treatment of hypodermatosis.Results and discussion. Recent studies have allowed for broadening and supplementing current ideas on the hypodermatosis prevention and treatment. Measures implemented in Russia and abroad against hypodermatosis can reduce the incidence and damage from this disease to low rates. Currently, the development of means to control hypodermatosis and a search for advanced diagnostic techniques has been continuing. Hypodectin is now one of the effective and quite safe medicines to treat animals’ skin in case of hypodermatosis. Injection drugs are also effective, particularly, Dermacin, Avermectin, Abamectin, Ivermectin, Novomec and Aversectin.